Oral language competence and restorative justice processes: refining preparation and the measurement of conference outcomes - Hennessey Hayes
Restorative justice conferencing for young offenders is a legislated response to youth offending, which has been in place in all Australian states and territories for nearly two decades. Restorative justice conferences are meetings between young offenders, their victims and supporters to discuss the offence, its impact and what the young person can do to repair harms caused by the offending behaviour. There is now a substantial body of research that has examined the impact restorative justice processes have on participants (eg how young offenders and victims judge the process). Results are largely positive, showing that participants view restorative justice processes as fair and they are satisfied with outcomes. Given the highly conversational nature of restorative justice conferencing processes however, this paper reviews research on oral language competence and youth offending. It raises questions about the need to refine preparatory work with young offenders and victims, to better understand young offenders’ capacities to effectively communicate in conference processes. It suggests that improved preparation (where language impairments in young offenders are identified and addressed) will lead to better outcomes for young offenders and victims